SOME RULE OF THE SPECULATION IN THE STOCK EXCHANGE (Research Bulletins of the Faculty of Economic Sciences, 2021)
Theaim of his paper is to presentation the issue of speculation In the Stock Ex-change. The theoretical issues related to speculationas well as presents technical basis and recommendations for future speculators.
Keywords: capital management, speculation on the stock exchange, stock marketsimulations